An evaluation of the effects of two different inoculants on the quality of potato hash silage for grower pigs - Sylvester, Thomas Ronald ([Bloemfontein?] : Central University of Technology, Free State, 2010)
This study evaluated the effects of two bacterial inoculants on the fermentation quality and aerobic stability of ensiled potato hash (PH) and on digestibility, growth performance and carcass characteristics of growing pigs fed the ensiled PH. In the first experiment, 700 grams of PH, was mixed with 300g wheat bran (as is basis) and ensiled in 1.5 litre anaerobic jars. The mixture had a dry matter (DM) of 41.3 g/kg, 78.05 g/kg DM of water-soluble carbohydrates (WSC) and a pH of 6.87 at day 0 and was treated with Bonsilage forte, BF, a heterofermentative LAB, Lalsil Fresh lactobacillus bachneri, LFLB, a homofermentative LAB or without LAB inoculant (control). Triplicate samples per treatment were collected on days 0, 3, 10, 21 and 45 post-ensiling and analysed for DM, WSC, pH, lactic acid (LA), acetic acid (AA), butyric acid (BA), propionic acid (PA) and ammonia-N. On day 45, the silage was subjected to aerobic exposure for 5 days and CO2 production was measured. In the second and third experiments, potato hash-wheat bran mixtures of 7:3 ratio were produced and ensiled in 210 litre drums that were kept at a 250C environment. The second experiment involved an apparent nutrients digestibility study using 30 female (Large White x Landrace crossbred) pigs (30 2 kg live weight), which were selected and housed individually. A cross-over design was applied with two periods and 30 animals fed 10 diets. Three pigs were given one diet per period. The diets were: commercial feed (control); 20, 40, and 60% dietary inclusion of potato hash silage (untreated potato hash silage, UPHS; Lalsil Fresh treated potato hash silage, LFLBPHS, and Bonsilage forte treated potato hash silage, BFPHS). Each experimental period lasted for eleven days with seven days being for adaptation to each diet and four days for collection of faeces before crossing over to the next treatment. Pigs were fed twice per day at 8:00 and 15:00, with the daily allowance equally divided between the two meals. Faecal samples were weighed and 10% of the total collection was taken and kept in a freezer at -180C. Prior to chemical analysis, individual samples of faeces were thawed and pooled for pigs within periods. Water was made available at all times through drinking nipples. The third experiment was a pig growth study using sixty-four crossbred pigs (Large White x Landrace) consisting of 32 males and 32 females (30.4±2.3kg live weight). The pigs were randomly allocated to four diets in a 4 x 2 (treatment x sex) factorial experiment in a completely randomised design. The diets contained up to 40% potato hash silage (PHS) and were: control (commercial diet - no silage), UPHS, BFPHS and LFLBPHS. Each experimental unit consisted of two pigs and each treatment was replicated 8 times. Pigs were fed on one of the four diets until they reached a slaughtering weight of 60 kg. Warm carcass weights were determined immediately after slaughter. After an overnight chill storage at 4.30C, cold carcass weights were determined. Carcass length was taken on hanging carcasses by measuring from the pelvic bone to the first thoracic vertebra, using a measuring tape. Backfat thickness was also taken on cold carcass at P2 (45 mm from midsection) between the 3rd and 4th rib on the left side of the pigs. Drip loss was also calculated for hanging carcasses by determining the weight loss after the overnight chill. Results from experiment 1 showed that both inoculants (LFLB and BF) reduced (P<0.05) the silage pH while increasing the LA content of silage compared to the control. The concentrations of propionic acid, butyric acid and ammonia-N were not affected by inoculation. When exposed to air, BF and LFLB reduced (P<0.05) CO2 production compared to the control. Results of the second experiment showed that daily intakes of organic matter (OM), crude protein (CP), ether extract (EE), acid detergent fibre (ADF), neutral detergent fibre(NDF), and gross energy (GE) were different (P<0.05) between diets. There were no differences (P<0.05) in digestibility of DM, EE, and DE among the treatments. However, diets containing 60% PHS had lower (P<0.05) NDF and ADF digestibility compared to diets containing less PHS. Furthermore, pigs on the control diet had higher (P<0.05) final body weight, average daily gain (ADG) and better feed conversion ratio (FCR) compared to those fed on other diets. Results of the third experiment showed that, pigs that were fed the control diet had higher (P<0.05) slaughter weight than pigs that were fed on diets containing PHS. There were no differences (P>0.05) on warm and carcass weight between diets containing PHS. Control had higher (P<0.05) dressing percentage than the other treatments. Drip loss percentage, backfat thickness, gastrointestinal tract (GIT), lungs and heart did not differ (P<0.05) between treatments. The effects of gender was not significant within treatments on slaughter weight, warm and cold carcass weights, dressing percentage, carcass length, backfat thickness, drip loss, GIT, lungs and heart. There were no gender by diet interactions (P>0.05) on warm carcass weights, cold carcass weights, drip loss percentage, carcass length, backfat, intergastral, lungs and heart. However, gender by diet interaction (P<0.05) occured on slaughter weight and dressing percentage. It was concluded that, inoculation improved both the fermentation and aerobic stability of PHS. Furthermore, there was no advantage in using LAB inoculants in ensiling potato hash on the growth performance or meat characteristics of growing pigs. However, further work is needed to evaluate the effects of higher dietary inclusion levels (> 60 %) of PHS on pig growth and reproductive performance.
Thesis (M. Tech.) -- Central University of Technology, Free State, 2010
Keywords: Central University of Technology, Free State - Dissertations; Swine - Feeding and feeds; Potatoes as feed; Silage - Handling; Silage - Fermentation; Microbial inoculants; Dissertations, academic|South Africa - Bloemfontein